Nudge: The Final Edition - Thaler, Richard H.; Sunstein, Cass R. (Sonipat: Penguin random House, 2021)
Since the original publication of Nudge more than a decade ago, the title has entered the vocabulary of businesspeople, policy makers, engaged citizens, and consumers everywhere. The book has given rise to more than 400 (3z(Bnudge units(3y (Bin governments around the world and countless groups of behavioral scientists in every part of the economy. It has taught us how to use thoughtful (3z(Bchoice architecture(3y$1 (Ba concept the authors invented$1 (Bto help us make better decisions for ourselves, our families, and our society.s
Includes acknowledgement, Notes and index
Keywords: Decision making$1 (BPsychological aspectss -- Behavioral economics -- Social influence; Consumer behavior -- Public policy